Proceedings of the 4th Asia Pacific Education Conference (AECON 2017) 2017
DOI: 10.2991/aecon-17.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Politeness Strategies in EFL Classroom: An Effect on building A Positive Values towards Students

Abstract: Abstract-Politeness is basically the study of knowing the way people use certain languages while they are having communication. In a language pedagogy, it does not rely on the Brown and Levinson theory of politeness to form the basis of teaching "politeness phenomena;" rather, there should be an attempt to raise cultural awareness. Moreover, it proposes the learning of politeness in a foreign language is a process of "reframing", re-analyzing existing frames regarding the linguistic behavior that generally occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…The result of this present study which revealed that the politeness strategies occurred in the classroom interactions was in line with some previous studies on politeness (Khusnia, 2017;Mahmud, 2019;Rahayuningsih et al, 2019;Senowarsito, 2013). Moreover, in this study, the finding also revealed that negative politeness strategy was mostly used in the classroom interactions with 8 out of 13 excerpts found.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The result of this present study which revealed that the politeness strategies occurred in the classroom interactions was in line with some previous studies on politeness (Khusnia, 2017;Mahmud, 2019;Rahayuningsih et al, 2019;Senowarsito, 2013). Moreover, in this study, the finding also revealed that negative politeness strategy was mostly used in the classroom interactions with 8 out of 13 excerpts found.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the politeness strategies can help to maintain the formality in doing presentation in the class. The study conducted by Khusnia (2017) and Umayah et al (2018) also indicated that politeness strategies have positive implications in students' attitude on language.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Students have a tendency to use positive politeness to demonstrate respect for lecturers who have more power and social status than students (Arif et al, 2018;Khusnia, 2017). A lecturer, on the other hand, employs a strategy with distinct preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Politeness is a positive attitude toward communication. It is a form of respect for others in social interactions (Khusnia, 2017;Jeanyfer & Tanto, 2018;Susanti et al, 2018;Yusuf & Anwar, 2019;Mahmud, 2019;Sapitri et al, 2020). Furthermore, according to Lakoff (1973), politeness is a type of communication attitude developed in society to avoid conflict.…”
Section: Politenessmentioning
confidence: 99%